Comparison of the physical fitness of older adult women according to the history of falls and the regular practice of different physical exercises - De Oliveira Reis, Mariana Rodrigues; Brazo-Sayavera, Javier; Lima, Jhennyfer Aline Rodrigues; Nogueira, Jonatas Evandro; Zago, Anderson Saranz [UNESP]; Trapé, Átila Alexandre (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2020)
Objectives: Comparing women's physical fitness according to the history of falls and regular practice of different physical exercises (combined training: strength and aerobic training; functional training: multicomponent; and multimodal training: two or more styles). Methods: A cross-sectional study was conducted with 44 women (aged between 50 and 80 years old). Sociodemographic data and history of falls in the last year were collected, in addition to anthropometric assessment and motor tests (flexibility, upper and lower limb strength, aerobic capacity and agility, and dynamic balance) to assess physical fitness. In the statistical analysis, independent samples t-test and ANCOVA using age, body mass index, and time of physical exercise as covariates were performed. Results: The participants who had falls in the last year presented worse outcomes in the flexibility tests (sit and reach and hands-on-the back), strength tests of upper limbs (elbow flexion), and lower limbs (sit and stand up), as well as aerobic capacity (six-minute walking test). Regarding the different modalities of exercises, it was not possible to observe statistical differences for any of the variables studied. However, satisfactory results according to the normative values were observed in the three groups. Conclusions: The group with a history of falls had worse outcomes in physical fitness. Regarding the different modalities of training, there was no difference between the groups for any variable analyzed. However, it seems that these modalities are essential to maintain satisfactory levels of physical fitness in the context of aging.
Comparação da aptidão física de mulheres adultas e idosas de acordo com o histórico de quedas e a prática regular de diferentes modalidades de exercícios físicos
Keywords: Accident Falls; Aging; Elderly; Physical Activity